Answer:
The answer is
<h2>
![\frac{3c}{4e}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3c%7D%7B4e%7D)
</h2>
Step-by-step explanation:
<h3>
![\frac{9 {c}^{3}d {e}^{2} }{12 {c}^{2} d {e}^{3} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B9%20%7Bc%7D%5E%7B3%7Dd%20%7Be%7D%5E%7B2%7D%20%20%7D%7B12%20%7Bc%7D%5E%7B2%7D%20d%20%7Be%7D%5E%7B3%7D%20%7D%20)
</h3>
To solve the fraction reduce the fraction with d
That's we have
<h2>
![\frac{9 {c}^{3} {e}^{2} }{12 {c}^{2} {e}^{3} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B9%20%7Bc%7D%5E%7B3%7D%20%20%7Be%7D%5E%7B2%7D%20%7D%7B12%20%7Bc%7D%5E%7B2%7D%20%7Be%7D%5E%7B3%7D%20%20%7D%20)
</h2>
Next simplify the expression using the rules of indices to simplify the letters in the fraction
<u>For c </u>
Since they are dividing we subtract the exponents
We have
<h2>
![{c}^{3} \div {c}^{2} = {c}^{3 - 2} = c^{1} = c](https://tex.z-dn.net/?f=%20%7Bc%7D%5E%7B3%7D%20%20%5Cdiv%20%20%7Bc%7D%5E%7B2%7D%20%20%3D%20%20%7Bc%7D%5E%7B3%20-%202%7D%20%20%3D%20c%5E%7B1%7D%20%20%3D%20c)
</h2>
<u>For </u><u>e</u>
<h2>
![e^{2} \div {e}^{3} = e^{2 - 3} = {e}^{ - 1} = \frac{1}{e}](https://tex.z-dn.net/?f=e%5E%7B2%7D%20%20%5Cdiv%20%20%7Be%7D%5E%7B3%7D%20%20%3D%20e%5E%7B2%20-%203%7D%20%20%3D%20%20%7Be%7D%5E%7B%20-%201%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7Be%7D%20)
</h2>
Substituting them into the expression we have
<h2>
![\frac{9c}{12e}](https://tex.z-dn.net/?f=%20%5Cfrac%7B9c%7D%7B12e%7D%20)
</h2>
Reduce the fraction by 3
We have the final answer as
<h2>
![\frac{3c}{4e}](https://tex.z-dn.net/?f=%20%5Cfrac%7B3c%7D%7B4e%7D%20)
</h2>
Hope this helps you
Answer:
Sitting fee - 32$
Step-by-step explanation:
This is a system of equations(let x represent the sitting fee)
x+6y=50
x+11y=65
You want to isolate the x variable - x+6y-6y=50-6y ; x = 50-6y
Input this into the 2nd equation: 50-6y+11y=65 ; 50+5y=65
Subtract 50 from both sides. 5y=15 (Divided 5y on both sides) ; y=3
Now that y = 3 input this into any equation I choose the 1st one.
x+6(3) = 50 ; x + 18 = 50 (Subtract 18 on both sides to get x)
x = 32
Prove: 32 + 6(3) = 50 ; 32+18 = 50 ; 50 = 50 True
C. 5/6
30 people with soda + 45 people with lemonade = 75/90 people
simplifies to 5/6.
Answer:
it would be a 85 percent
Step-by-step explanation:
Step-by-step explanation:
Case 1 :
![3x + 2y = 6 \\ 4x + y = 2 \\ 3x = 6 - 2y \\ x = \frac{6 - 2y}{3} = \\ x = 2 - \frac{2y}{3} \\ 4(2 - \frac{2y}{3} ) + y = 2 \\ 8 - \frac{8y}{3} + y = 2 \\ - 1.67y = - 6 \\](https://tex.z-dn.net/?f=3x%20%2B%202y%20%3D%206%20%5C%5C%204x%20%2B%20y%20%3D%202%20%5C%5C%203x%20%3D%206%20-%202y%20%5C%5C%20x%20%3D%20%20%5Cfrac%7B6%20-%202y%7D%7B3%7D%20%20%3D%20%5C%5C%20x%20%3D%202%20-%20%20%5Cfrac%7B2y%7D%7B3%7D%20%20%5C%5C%204%282%20-%20%20%5Cfrac%7B2y%7D%7B3%7D%20%29%20%2B%20y%20%3D%202%20%5C%5C%208%20-%20%20%5Cfrac%7B8y%7D%7B3%7D%20%20%2B%20y%20%3D%202%20%5C%5C%20%20-%201.67y%20%3D%20%20-%206%20%5C%5C%20)
![y = 3.59 \\ x = 2 - \frac{2y}{3} \\x = 2 - \frac{2 \times 3.59}{3} \\ \\ x = - 0.39](https://tex.z-dn.net/?f=y%20%3D%203.59%20%5C%5C%20x%20%3D%202%20-%20%20%5Cfrac%7B2y%7D%7B3%7D%20%20%5C%5Cx%20%3D%20%202%20-%20%20%5Cfrac%7B2%20%5Ctimes%203.59%7D%7B3%7D%20%20%5C%5C%20%20%5C%5C%20x%20%3D%20%20-%200.39)
Case 2 :
![3x + 2y = 6 \\ 4x - y = 2 \\ x = 2 - \frac{2y}{3} \\ 4(2 - \frac{2y}{3} ) - y = 2 \\ 8 - \frac{8y}{3} - y = 2 \\ - 3.67y= - 6 \\ y = 1.63](https://tex.z-dn.net/?f=3x%20%2B%202y%20%3D%206%20%5C%5C%204x%20%20-%20%20y%20%3D%202%20%5C%5C%20x%20%3D%202%20-%20%20%5Cfrac%7B2y%7D%7B3%7D%20%20%5C%5C%204%282%20-%20%20%5Cfrac%7B2y%7D%7B3%7D%20%29%20-%20y%20%3D%202%20%5C%5C%208%20-%20%20%5Cfrac%7B8y%7D%7B3%7D%20%20-%20y%20%3D%202%20%5C%5C%20%20%20-%203.67y%3D%20%20-%206%20%5C%5C%20y%20%3D%201.63)
![x = 2 - \frac{2y}{3} \\ x = 2 - \frac{2 \times 1.63}{3} \\ x = 2 - 1.087 \\ x = 0.913](https://tex.z-dn.net/?f=x%20%3D%202%20-%20%20%5Cfrac%7B2y%7D%7B3%7D%20%20%5C%5C%20x%20%3D%202%20-%20%20%5Cfrac%7B2%20%5Ctimes%201.63%7D%7B3%7D%20%20%5C%5C%20x%20%3D%202%20-%201.087%20%5C%5C%20x%20%3D%200.913)